2021
DOI: 10.7759/cureus.15163
|View full text |Cite
|
Sign up to set email alerts
|

Stimulant Usage by Medical Students for Cognitive Enhancement: A Systematic Review

Abstract: Stimulants have been used throughout human history for a variety of reasons. High levels of stress and the demanding nature of medical school make their usage among medical students particularly common. The most prevalent stimulant used by students is coffee, followed by tea and other forms of caffeine like sugary energy drinks. In addition, amphetamine-based medications for treating attention deficit hyperactivity disorder (ADHD) have been increasing in popularity, which many students take illicitly. Students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
16
0
2
Order By: Relevance
“…The most prevalent stimulant used by students is coffee, followed by tea and other forms of caffeine like sugary energy drinks. 17 The results of our study reported that the consumption of tea and coffee were 94 (37.6%) and 34 (13.6%) respectively. Another study conducted among the university students of Lebanon revealed that the use of caffeine during exams was more than the required dose approved by Food and Drug Administration (FDA).…”
Section: Discussionmentioning
confidence: 55%
“…The most prevalent stimulant used by students is coffee, followed by tea and other forms of caffeine like sugary energy drinks. 17 The results of our study reported that the consumption of tea and coffee were 94 (37.6%) and 34 (13.6%) respectively. Another study conducted among the university students of Lebanon revealed that the use of caffeine during exams was more than the required dose approved by Food and Drug Administration (FDA).…”
Section: Discussionmentioning
confidence: 55%
“…In our study, caffeine, in different forms, was the most often chosen CEs by our respondents (over 92%). It is estimated that about 80–85% of the adult world’s population uses caffeine because of caffeine-induced psycho-stimulation [ 31 , 32 , 33 , 34 ]. Our results are consistent with some other published data [ 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This observation is unsurprising because students (over 90%) often used caffeine as a CE. It was found that caffeine may produce rapid positive inotropic and chronotropic effects on the cardiovascular system and, in toxic doses, may cause life-threatening arrhythmias [ 34 , 48 ]. Caffeine can activate various brain areas [ 48 ], which is the reason for increased alertness but may lead to sleeping problems.…”
Section: Discussionmentioning
confidence: 99%
“…Existen factores externos que pueden afectar directamente la calidad del sueño de las personas, como lo son: el uso de estimulantes para la mejora cognitiva, entre los que están los fármacos promotores de vigilia, sustancias psicoactivas, bebidas energéticas y productos con cafeína (1,24). Entre los efectos adversos del uso excesivo de estos productos se encuentran: el riesgo de toxicidad, la disminución de la calidad y cantidad de sueño; efectos que opacan los pros de su uso y consumo (24). Según un estudio de revisión sistemática realizado en 2021, el uso de estimulantes para la mejora cognitiva es cada vez más común en los estudiantes de medicina, pues según ellos, ayuda a prolongar la vigilia y mantener la concentración durante amplios períodos (24).…”
Section: Factores Que Influyen En La Calidad Del Sueñounclassified
“…Entre los efectos adversos del uso excesivo de estos productos se encuentran: el riesgo de toxicidad, la disminución de la calidad y cantidad de sueño; efectos que opacan los pros de su uso y consumo (24). Según un estudio de revisión sistemática realizado en 2021, el uso de estimulantes para la mejora cognitiva es cada vez más común en los estudiantes de medicina, pues según ellos, ayuda a prolongar la vigilia y mantener la concentración durante amplios períodos (24). Entre las razones de los estudiantes para el uso y consumo de estas sustancias se encuentra el mejoramiento del rendimiento académico pues les permite estar alerta y concentrados en sus actividades prácticas y teóricas, además de lograr una productividad prolongada a lo largo del día; estas situaciones los lleva al aumento del consumo de estas sustancias en temporada de exámenes y culminación de año universitario (24).…”
Section: Factores Que Influyen En La Calidad Del Sueñounclassified